ANALISIS SISTEM TANGGAP DARURAT KEBAKARAN DI CONTAINER YARD 02 TERMINAL PETIKEMAS PT. PELABUHAN INDONESIA III (PERSERO) SEMARANG TAHUN 2016 - Grandis Harini Sambada; Bina Kurniawan; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Container Yard PT. Pelabuhan Indonesia III Semarang is large port giving services on manual handling container. A fire at the container terminal can cause a great deal of loss as it affects a high value of asset, work process and employment opportunities. One of the effort to decrease the risk and impact due to the fire is the emergency response system. One of efforts to reduce the risk and impact caused by the fires is require the application of non-structural mitigation in multi-storey office building. The purpose of the study is to analyze the emergency response system in the effort to prevent and control a fire disaster at terminal Container Yard 02. This research is a Descriptive Qualitative research with in-depth interviews and yard observation. The subjects of this study consists of 5 people as the main informants and 3 people as informant triangulation. The results show that the management has the commitment and written policy for Occupational Safety and Health, dated and certified by the highest leader atau level. Fire drills training are given to all staffs and the emergency response team. Container Yard 2 has all the facilities in active preventive fire such as APAR and hydrant and safety lives facilities that is the meeting point. The procedure taken in an emergency situation is the scenario in fire simulation. In emergency cases the communication system to inform and request help to the related parties is in place. The conclusion of this study is that in Terminal Container the emergency response is applied, such as fire simulation, socialization of the fire prevention policy and training on fire extinction and victim evacuation.